Relationship Between Neoadjuvant Chemotherapy and Log Odds of Positive Lymph Nodes and Their Prognostic Role in Advanced Ovarian Cancer Patients With Optimal Cytoreductive Surgery - Hou, Yue-min; Xue, Yan; Yao, Jin-meng; Feng, Fang; An, Rui-fang (Frontiers in Oncology, 2022)
Purpose To analyze the relationship between neoadjuvant chemotherapy (NACT) and log odds of positive lymph nodes (LODDS), as well as their prognostic role in advanced ovarian cancer (AOC) patients with optimal cytoreductive surgery. Patients and Methods From the SEER database during 2010-2016, we identified 1,012 AOC patients with optimal cytoreductive surgery. Univariable and multivariable logistic regression was performed to identify the relationship between NACT and LODDS. Overall survival (OS) and cancer-specific survival (CSS) were assessed using the Kaplan-Meier method and log-rank test. Univariable and multivariable Cox regression was conducted to determine the independent prognostic factors for OS and CSS. Results Factors associated with significantly higher NACT odds included older (≥60 years old), married, tumor size ≥ 15 cm, FIGO IV, and LODDS ≤ 0.1. Multivariable Cox regression model confirmed older (≥60 years old), unmarried, separated, divorced, widowed, mucinous histology type, tumor size ≥ 15 cm, and LODDS > 0.1 were correlated with increased risks of OS and CSS. NACT was not an independent prognostic factor for OS and CSS. In the subgroup analyses, LODDS was an independent prognostic factor for OS and CSS in patients with < 75 years old, married, unmarried, FIGO III, and tumor size < 15 cm. Conclusion NACT did not show any survival benefit in AOC patients with optimal cytoreductive surgery, but it may be beneficial in reducing LODDS. Meanwhile, clinicians can use grade of LODDS to predict the prognosis of AOC patients with optimal cytoreductive surgery.